DESKRIPSI KEPALA KELUARGA YANG MENIKAHKAN ANAK WANITANYA PADA USIA MUDA - Inggrit Artiana Devi; Buchori Asyik; Edy Haryono (JPG (Jurnal Penelitian Geografi), 2013)
This study aimed to describe the marriage of young women in the Mataram Udik villageBandar Mataram District Centre Lampung regency year 2012, with mainly focused of studyon the level of income, level of education, and views of life. This study used descriptiveresearch method, the object of this study was the head of the family that her daughtermarried off at a young age. The data collectives through observation, interviews,questionnaires and documentation. Data analyzes is using the percentage table as basicinterpretation and described as a research report. The results of this study show that: (1)Income of the head of families who marry off their daughter at the young age was low(≤ Rp 982.000,-) caused young age marriage. (2) The education level families who marryoff their daughter at a young age was low (SD dan SMP). (3) Views of life the head offamilies who marry off their daughter at a young age are: (a) their daughter had little desireto continued their school. (b) parents had opinion that through young age marriage so theycan decrease their daughters’ financial burden. (c) there was custom among people whothink that girls who not married yet until twenty called old maid.Key words: early marriage, parents, income, education, view of life